IbM Kelompok Masyarakat Pesisir Terhadap Perlindungan dan Pengelolaan Lingkungan Hidup di Desa Pria Laot Kota Sabang - Yusra; Eliana; Dahlan (AJAD : Jurnal Pengabdian kepada Masyarakat, 2021)
The purpose of this service is to provide solutions by implementing Science through the Science and Technology program for the community at the STIES Research and Community Service Center to carry out advocacy and legal consultation to the community in Batee Shok Juroeng Pria Laot Village, Sukakarya District, Sabang City in order to minimize conflict and grant authority. local communities in the protection and management of the environment, especially the management of resources in coastal areas. The method used in IbM activities with a social approach, implementing Legal Counseling and Program Strategies for Coastal Mangrove Forest Management Community Groups, activities carried out by Focus Group Discussion (FGD), and implementation involving students as part of learning in the ways and processes of resolving environmental disputes related to with a Subject in Environmental Law and Management Economics. The conclusions of the service activities are; 1) The establishment of environmental law awareness for coastal communities to maintain and protect coastal resources in residential areas, 2) Form and reorganize the Coastal Management Community Group, and 3) Open access for people outside Batee Shok Village to utilize supporting facilities and infrastructure. Sabang City National Park Tourism.